Reconstructing Ontology, Epistemology, and Axiology as the Basis for Transforming Islamic Religious Education in the Society 5.0 Era - Mukhtar, Dertha; Ahida, Ridha (The Future of Education Journal, 2025)
This article discusses the reconstruction of ontology, epistemology, and axiology as the philosophical foundation for the development of Islamic Religious Education (PAI) in the Society 5.0 era. This era is characterized by the integration of digital technology, artificial intelligence (AI), and big data in human life, requiring Islamic education to undergo a philosophical transformation. Through a literature review and philosophical analysis approach, this article asserts that ontological reconstruction places humans as multidimensional beings serving as both servants of God and stewards of the earth. The epistemology of Islamic education in this era integrates revelation, reason, and digital data, while its axiology aims to form the perfect human being (insan kamil) with noble character, critical thinking, and adaptability to technological change. The implication is that Islamic Religious Education should be developed through an integrative-holistic model, Islamic-based technology, and character-oriented spirituality. This study proposes a transcendental-progressive paradigm of Islamic education that upholds divine values while advancing technological mastery for the benefit of humanity.